The Association of Psychological Stressors With Cannabis Use During Pregnancy: Findings From the National Survey on Drug Use and Health 2017–2019. Issue 8 (30th August 2022) - Vadukapuram, Ramu; Chaudhari, Gaurav; Trivedi, Chintan; Vora, Darshini; Memon, Aksha; Giri, Deepali; Tazin, Faria; Reddy, Preetam; Mansuri, Zeeshan; Jain, Shailesh Bobby
Abstract: Even though marijuana is illegal on the federal level, it is one of the most used drugs in the United States during pregnancy. Our study investigates the relationship between numerous socioeconomic, demographic, and mental health risk variables and substance use during pregnancy. We examined data from the National Survey on Drug Use and Health from 2017 to 2019. Compared with the no serious psychological distress (SPD) group, the odds of using cannabis were higher in pregnant women with past-month SPD. In this study, in comparison with unmarried pregnant women, married pregnant women had a 67% lower chance of currently using cannabis. Racially, Hispanic pregnant women had 3 to 4 times higher odds for current use of cannabis as compared with the other races. Preventing cannabis use and its adverse effects by screening pregnant women could be part of the current strategy for reducing cannabis use.